Effect of Work Conflict, Work Stress and Satisfactionworking on Employee Erformance at PT. Federal International Financegroup (FIF-Group)Sidoarjo - Wiwid Ida Risnawati; Mudji Astuti; Toyirova Shaxlo; Ismatova Dilafruz; Kodirova Dilnoza (Research Parks Publishers, 2022)
This study aims to determine Work conflicts, Job Stress and Job Satisfaction on Employee Performance of PT. Federal International Finance Group (Fif-Group) Sidoarjo. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 30 employees at PT. Federal International Finance Group (Fif-Group) Sidoarjo. The analysis tools used in this study are multiple linear regression analysis, multiple correlation coefficient (R), and classical assumption test using SPSS version 18 for windows. Primary data in this study were obtained from questionnaires which were measured using a Likert scale which was tested for validity and reliability. The results of this study prove that work conflict affects employee performance, job stress affects employee performance and job satisfaction also affects employee performance. job satisfaction variable that most influences employee performance.